Transcribed and non-transcribed regions of Tetrahymena ribosomal gene chromatin have different accessibilities to micrococcal nuclease. - Palen, T E (1983)
DNA renaturation kinetics was used to examine the relative accessibility of various regions of the Tetrahymena ribosomal RNA gene (rDNA) chromatin to micrococcal nuclease. In nuclei from cells active in rRNA transcription, the transcribed region of the rDNA chromatin was as much as 5-fold more accessible than the average of the total chromatin. As few as 20% inactive genes in the population could have accounted for all of the hybridization, so the transcribed region of the active units may be totally unprotected from nuclease degradation. The terminal non-transcribed spacer downstream from the transcription unit was also preferentially digested, but to a smaller degree. The central non-transcribed spacer was degraded to the same extent as total chromatin after a high degree of nuclease digestion. In nuclei from starved cells, which have 96% reduced rRNA transcription, the transcribed and terminal spacer regions of the rDNA were again more accessible than the total chromatin from the same nuclei, but the difference did not exceed 2-fold. We conclude that transcriptional activation is accompanied by major changes in the structure of the ribosomal gene chromatin, and that the extent and/or type of structural alteration differs in each functionally defined region of the rDNA.